A new species of Byttneria sect. Crassipetala (Malvaceae, Byttnerioideae) from Eastern Amazonia - Gerace, Samuele; Colli-Silva, Matheus (Phytotaxa, 2024)
Byttneria (Malvaceae, Byttnerioideae) is a Pantropical genus known for its variable growth forms—ranging from shrubs to lianas—and complex floral structures. In this study, we describe a new species, Byttneria filifolia Gerace & Colli-Silva, from B. sect. Crassipetala, found in the Eastern Amazon rainforest of Brazil, specifically in Pará, and Mato Grosso states. Byttneria filifolia is distinguished from its relatives by its filiform leaves, as well as by the multiaperturate leaf nectary, growth form, leaf shape, and petal morphology. This study contributes to our comprehension of morphological patterns within Byttneria from the Amazon rainforest, underscoring the role of morphological features in species delineation.